Pengaruh Kualitas Pelayanan Produk, Promosi, Harga Dan Distribusi Terhadap Minat Beli Kembali Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Mediasi - Sujana, Cecep; Firdaus, M. Riza; Ahmad Rifani (Universitas Lambung Mangkurat, 2024)
The main objective of this research is to test and analyze the influence of service quality, product, promotion, price and distribution on customer repurchase interest with customer satisfaction as a mediating variable. The data analysis method used is Partial Least Square (PLS), with the help of SmartPLS3.0 progam. The results of this research show that the variables that have a significant influence on satisfaction are Service Quality and Product. Meanwhile, Promotion, Price and Distribution do not have a significant direct effect on Customer Satisfaction. Apart from that, service quality, products, promotions, distribution and customer satisfaction have a direct and significant influence on repurchase interest. Meanwhile, price has no significant effect on repurchase interest